2019
DOI: 10.1186/s40880-019-0386-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD137 expression through K‐Ras signaling in pancreatic cancer cells

Abstract: Background The interaction between CD137 and its ligand (CD137L) plays a major role in the regulation of immune functions and affects cancer immunotherapy. CD137 is a cell surface protein mainly located on activated T cells, and its regulation and functions in immune cells are well established. However, the expression of CD137 and its regulation in cancer cells remain poorly understood. The main purposes of this study were to examine the expression of CD137 in pancreatic cancer cells and to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Choi et al reported that antitumor immunity is enhanced in 4-1BBDKO mice as a result of the increase in NK cells due to the shift of the dominant type of immune cells from the innate NK cell to the adaptive Tc via 4-1BB signaling [ 167 ]. It is known that constitutive activation of oncogenic KrasG12D, which approximately 90% of pancreatic cancer incidences exhibit, upregulates 4-1BB in tumor cells through MAPK and NF-κB signaling [ 168 , 169 ]. Therefore, many clinical CAR-T cell trials in pancreatic cancer are also using the 4-1BB receptor, targeting mesothelin, MUC1, CD19, CD133 ( Table 1 ).…”
Section: Transcriptional and Epigenetic Reprogramming Of T-cell Exmentioning
confidence: 99%
“…Choi et al reported that antitumor immunity is enhanced in 4-1BBDKO mice as a result of the increase in NK cells due to the shift of the dominant type of immune cells from the innate NK cell to the adaptive Tc via 4-1BB signaling [ 167 ]. It is known that constitutive activation of oncogenic KrasG12D, which approximately 90% of pancreatic cancer incidences exhibit, upregulates 4-1BB in tumor cells through MAPK and NF-κB signaling [ 168 , 169 ]. Therefore, many clinical CAR-T cell trials in pancreatic cancer are also using the 4-1BB receptor, targeting mesothelin, MUC1, CD19, CD133 ( Table 1 ).…”
Section: Transcriptional and Epigenetic Reprogramming Of T-cell Exmentioning
confidence: 99%
“…However, the regulatory mechanisms and the significance of CD137 expression in cancer cells remain largely unknown. A recent study has shown that CD137 expression in pancreatic cancer cells might be positively regulated by oncogenic K-ras [9]. Using a K-ras-inducible cell system and cancer cell lines with various K-ras status, the authors demonstrated that K-ras could induce CD137 expression through mitogen-activated protein kinases (MAPK) and NF-κB signaling pathways.…”
mentioning
confidence: 99%
“…The NF-κB pathway seems mainly activated by extracellular IL-1α (interleukin-1 alpha), whose expression and secretion are enhanced by K-ras [12]. In contrast, the MAPK pathway is stimulated by K-ras activation without the involvement of IL-1α [9]. It is currently unclear how the activation of K-ras could lead to increased expression of IL-1α, or which transcription factor(s) might bind and regulate the CD137 transcription in cancer cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations